2010
DOI: 10.1517/13543776.2010.530659
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the embryonic gene Cripto-1 in cancer and beyond

Abstract: Importance of the field-Emerging evidence has clearly implicated an inappropriate activation of embryonic regulatory genes during cell transformation in adult tissues. An example of such a case is the embryonic gene Cripto-1. Cripto-1 is critical for embryonic development and is considered a marker of undifferentiated embryonic stem cells. Critpo-1 is expressed at low levels in adult tissues, but is re-expressed at a high frequency in a number of different types of human carcinomas, therefore representing an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Cripto functions as an obligatory coreceptor for Nodal, GDF1, and GDF3 but antagonizes activin A and TGF-␤ (33,34,43,(45)(46)(47). The expression of Cripto has been described to be silent in the postnatal situation, except in a few aberrant cases, such as epithelial cancers or melanomas (48). Therefore, the expression of Cripto in myogenic cells is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Cripto functions as an obligatory coreceptor for Nodal, GDF1, and GDF3 but antagonizes activin A and TGF-␤ (33,34,43,(45)(46)(47). The expression of Cripto has been described to be silent in the postnatal situation, except in a few aberrant cases, such as epithelial cancers or melanomas (48). Therefore, the expression of Cripto in myogenic cells is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports established that CRIPTO1 is expressed in various tumors, but not in normal tissues (29). We assessed CRIPTO1 expression in 21 resected snap-frozen NSCLC tumor samples by Western blot.…”
Section: Cripto1 Is Expressed In Nsclc Tumors But Not In Cell Linesmentioning
confidence: 95%
“…CRIPTO1 was originally isolated from human undifferentiated NTERA-2 embryonic carcinoma cells and is not expressed in most adult tissues (27,28). High levels of CRIPTO1 expression have been reported in a variety of human carcinomas (29) and associated with poor prognosis in gastric (30), colorectal (31), and breast cancer (32) patients. In vivo studies showed that ectopic CRIPTO1 expression induced epithelial-to-mesenchymal transition (EMT), and MMTV-CRIPTO1 transgenic mice developed hyperplasias and tumors in the mammary gland (33).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the block of Cripto signaling with an anti-CFC domain antibody determined a strong inhibition of tumor cell growth in vivo [ 34 ]. Ever since, different approaches based on the use of oligonucleotides, vaccines or antibodies have been successfully applied to target Cripto by inhibiting its activity and/or expression in tumors and in neurodegenerative diseases [ 35 ]. Cripto inhibition by different approaches always resulted in inhibition of cancer cell proliferation in vitro and of tumor growth in vivo [ 36 ].…”
Section: Introductionmentioning
confidence: 99%